Peran Badan Permusyawaratan Desa dalam Pengelolaan Dana Desa - Rika Wulandari; Abdul Kadir; Yurial Arief lubis (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2021)
The Purpose of this study is to describe the role of Village Consultative Body in fund management village in the form of concrete rebate constuction for the 2017 fiscal year in the Sei Merbau Village District Ujung Padang Regency Regency of Simalungun next constraints. Validity of the data whit the triangulation of source and collection techniques data. Analysis was performed whit a model interactive, reduction data, presentation data, and drawing conclusions. This study uses kualitative approach with data collection trough interviews, observation, and documentation. The Subject of this studi is the head and village, cairmand and BPD member, and the community in the village Sei Merbau district Ujung Padang regency of Simalungun. Object under investigation is the role BPD in management village fund in the village Sei Merbau District of Ujung Padang. The result of study this study indicate that role of BPD in the village fund management was not optimal, measured by the fuor indicators, namely three indicators can be categorized as good including equality, consensus orientation and participation. But there is one indicators that is not optimal, namely Rresponsiveness. As for the inhibiting factor include Human Resources and delay in project implementation.